Climate Adaptation Modelling - Kondrup, Claus; Mercogliano, Paola; Bosello, Francesco; Mysiak, Jaroslav; Scoccimarro, Enrico; Rizzo, Angela; Ebrey, Rhian; Ruiter, Marleen de; Jeuken, Ad; Watkiss, Paul (Springer Climate,, 2022)
This open access book focuses on an issue only marginally tackled by this literature: the still existing gap between adaptation science and modelling and the possibility to effectively access and exploit the information produced by policy making at different levels, international, national and local. To do so, the book presents the proceedings of a high-level expert workshop on adaptation modelling, integrated with main results from the "Study on Adaptation Modelling" (SAM-PS) commissioned by the European Commission's Directorate-General for Climate Action (DG CLIMA) and implemented by the CMCC Foundation - Euro-Mediterranean Centre on Climate Change, in collaboration with the Institute for Environmental Studies (IVM), Deltares, and Paul Watkiss Associates (PWA). What is the latest development in adaptation modelling? Which tools and information are available for adaptation assessment? How much are they practically usable by the policy community? How their uptake by practitioners can be improved? What are the major research gaps in adaptation modelling that needs to be covered in the next future? How? This book addresses these questions presenting the results of a study on adaptation modelling commissioned by the European Commission's Directorate-General for Climate Action (DG CLIMA) enriched by the outcomes of a high-level expert workshop on adaptation also part of the research. This book aspires to provide a useful support to academics, policy makers and practitioners in the field of adaptation to orient them in the expanding adaptation modelling assessment literature and suggest practical ways for its application. This book, mainly addressed to academics, policy makers and practitioners in the field of adaptation, aims to providing orientation in the large and expanding methodological/quantitative literature, presenting novelties, guiding in the practical application of adaptation assessments and suggesting lines for future research. .